CRFK and Primary Macrophages Transcriptomes in Response to Feline Coronavirus Infection Differ Significantly - Drechsler, Yvonne; Vasconcelos, Elton J. R.; Griggs, Lisa M.; Diniz, Pedro P. P. V. (Frontiers in Genetics, 2020)
Coronaviruses are highly infectious and common in many species, including in humans, and agricultural and domestic animals. Host responses play an important role in viral entry, replication, assembly, and pathogenesis, although much is still to be understood, particularly host-virus interactions. Feline coronavirus is highly contagious, and ubiquitous in virtually all cat populations. Host-pathogen interactions have not been studied extensively due to the complex pathogenesis and development of clinical disease. Few studies have investigated cellular host responses to feline coronavirus infection, particularly at early time points. Transcriptome studies based on next-generation sequencing has the potential to elucidate the early responses of cells after viral infection and, consequently, give further insight into the pathogenesis of viruses. The current study aims to characterize and compare the viral- and immune-related differentially expressed genes in response to the coronavirus FIPV across different time points in a cell line which is permissive for productive replication versus primary cells implicated in pathogenesis. When comparing host responses in CRFK to primary macrophages, many differences were observed with regards to expressed genes and their enrichments for both KEGG pathways and GO terms. CRFK cells which are permissive for productive replication of FIPV, showed induction of a large network of immunological and virally induced pathways. In contrast, Macrophages did not show similar host responses, with stronger pathway enrichment in downregulated transcripts. This study provides insights to better understand gene transcription in immune cells compared to epithelial cells discerning pathways relevant to pathogenesis in the early stages of infection.